Educational Values in Saprahan Tradition in The Malay Community of Sambas District - Ramadhan, Dendy (The Pontianak State Institute of Islamic Studies, 2018)
This article discusses the local wisdom of the Malay culture of Sambas Regency that is the Saprahan tradition. The saprahan tradition is derived from Sambas Malay culture’s, the core activity of it is eating together which is done at big events such as marriage, salvation, and so on. In eating together, each group consists of 1 to 6 people in one saprahan, then a tarup is made. Tarup is a place that is used at important events filled with illegal activities for men and eating saprahan. This tradition contains values that are in line with the value of Islamic education. The community is taught the value of togetherness, good relations, removing ego, willingness to share, friendliness, ethics, and self-esteem.